A cidade do Salvador e a sua centralidade(The city of Salvador and its centrality) - Noelio Spinola; Paulo Patricio Costa; Tatiana Santiago (European Regional Science Association (ERSA), 2015)
This text is linked to the question of urban centrality of the city of Salvador, capital of Bahia State, that was examined upon two perspectives regarding its historical background. Firstly, the centrality in regional terms - the influence of the old capital in relation to its surrounding region and secondly according to the centrality of the city in terms of its own internal space. The text leads to the realization about the two centralities correlating directly, demonstrating that changes in regional centrality affect urban centrality as well the process of occupation and land use in the city. On the other hand, the largest and most important assets are the core of a larger city the bigger tends to be its area of influence. In the current circumstances, to the extent that the influence of Salvador upon its surroundings is reduced, by external reasons, the city got transformed itself from monocentric into polycentric and their spaces are expanded due to the migration of poor populations that put overwhelming pressure upon its ability to provide physical infrastructure and urban social support according with its size and dimension. However when considering the type of occupation that occurred in the periphery, where the ruling was the low-income and poor instructional level, which saw was the dissemination of 'centers of subsistence' equipped with central goods of limited range and reduced threshold without greater power of polarization. Salvador was poor and attracted poorest consolidating in a low-income city position.
Keywords: R12; R11; 330; City; centrality; urban; regional; Salvador